2015
DOI: 10.1186/s12910-015-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring researchers’ experiences of working with a researcher-driven, population-specific community advisory board in a South African schizophrenia genomics study

Abstract: BackgroundCommunity engagement within biomedical research is broadly defined as a collaborative relationship between a research team and a group of individuals targeted for research. A Community Advisory Board (CAB) is one mechanism of engaging the community. Within genomics research CABs may be particularly relevant due to the potential implications of research findings drawn from individual participants on the larger communities they represent. Within such research, CABs seek to meet instrumental goals such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Recruitment of study participants depends to a large extent on buy-in from local communities in the target population [22]. Therefore engaging community members and stakeholders in the planning phase has become an important aspect of research projects [23].…”
Section: Community Engagementmentioning
confidence: 99%
“…Recruitment of study participants depends to a large extent on buy-in from local communities in the target population [22]. Therefore engaging community members and stakeholders in the planning phase has become an important aspect of research projects [23].…”
Section: Community Engagementmentioning
confidence: 99%
“…Many of us also echoed concerns about engaging marginalized communities in genomics research given limited health and genomics literacy, 6 as well as resistance within the Black community. A Black community clinician remarked that some Blacks would prefer “keeping their heads in the sand” instead of seeking out information about their own health.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 It can be difficult to engage marginalized communities in genomics and precision medicine research, due both to familiar barriers to community engagement (e.g., mistrust) and more genomic-specific challenges (e.g., its highly technical language). 6,7 Unfortunately, there is limited information available regarding formation of substantive collaborations to navigate the complex intersection of ancestry, race, genomics and health.…”
mentioning
confidence: 99%
“…The Preceded information ascertained that stigma associated with mental illness have many ethical implications in the context of Responsible Conduct of research (RCR). These ethical implications can be seen in the form of issues related to consent form (Fisher & Oransky, 2008;Vaz & Srinivasan, 2014), fair treatment and good respect for individual rights concerning treatment choices (Carrier, Banayan, Boley, & Karnik, 2017;Corcoran, 2016), use of various forms of treatments, participation in the clinical studies at the national level and issue of possible use of data for national or governmental purpose (Alahmad, Al-Jumah, & Dierickx, 2012;Ayalon, Karkabi, Bleichman, Fleischmann, & Goldfracht, 2015;Campbell et al, 2015;Sharma et al, 2013;Vaz & Srinivasan, 2014). Indeed, scientific researchers and those who are conducting research studies about mental health in the primary health care settings (Dubois et al, 2011); must consider the applications of ethical standards as suggested by RCR with cautions.…”
Section: Implications Of Mental Illness Stigma For Research and Ethicsmentioning
confidence: 99%